No escape: most insect colonisers of an introduced fig tree in Cyprus come from the plant’s native range - Compton, Stephen G.; Stavrinides, Menelaos; Kaponas, Chrysos; Thomas, P. J. (My University, 2020)
Plants that become invasive outside their native range often benefit from the absence of their native-range herbivores. Ficus microcarpa is a widely-planted Asian–Australasian species of fig tree that has become invasive in parts of its introduced range. As in most places where it is planted, the pollinator of F. microcarpa has been introduced to Cyprus, together with at least six other Asian fig wasp species. We recorded the other insects feeding on the leaves, buds and stems of this fig tree in southern Cyprus. Eight sap-sucking insects were recorded, and one leaf-galling species, with some present at high frequencies and densities. The insects were a mix of introduced polyphagous species and introduced F. microcarpa specialists. They included the first European record of the fig leaf galling psyllid Trioza brevigenae, which was described from India. Ficus microcarpa has not escaped from its native-range phytophages, but they appear to be free of their own specialist parasitoids and predators. The result is a herbivore load than may be comparable with what the plant experiences in its countries of origin. This is likely to reduce the invasiveness of F. microcarpa, but at the same time makes the plant a less attractive option for future planting.
Keywords: Biological control; Ficus microcarpa; Street trees; Trophic cascades